(untitled) (Archaeologia Adriatica, 2009)
The article discusses various examples of fortification in the area of the prefecture of Illyricum, extending from the Mediterranean Noricum and Dalmacia all the way to Epirus and Achaea, which are attributed to the Justinian period. For eastern Illyricum exist the extensive documents of Procopius, with partial descriptions of cities, settlements, and military fortifications, which require critical evaluation so establish an accurate insight into the extent of Justinian’s activities. Data of this type – with several small exceptions – do not exist for western Illyricum, but archaeological excavations and field surveys of the well-preserved architecture in the Mediterranean section have enabled dating of buildings and the renovation of numerous structures in the Justinian period. These significant changes in the settlement structure of late Antiquity can be characterized as the "kastronization" of settlements and territories and the "transition from polis to kastron". In the article the author attempts, in comparison with better known examples of fortification in eastern Illyricum cited in sources, to seek parallels in western Illyricum and to present the similarities and differences between them. The author will show the different categories of towns and their transformation, as well as the occasional defensive structures already dated in more detail to the Justinian period. For fortification in the area he will briefly delineate the state of research in the various regions of the prefecture of Illyricum, and for several better investigated examples display the fundamental characteristics of the construction of the military fortifications and settlements. In somewhat more detail will be presented the later defensive elements of fortifications in Dalmatia, Bosnia, Slovenia, and Austria. Several examples of lines of defensive barriers will also be noted.